PEMBERIAN TANAH KEPADA SESEORANG SEBAGAI SOLUSI DALAM MENGATASI KELALAIAN AHLI WARIS - Effendi, Devi Rianti (UNES Law Review, 2020)
The Indonesian state, which has the concept of the relationship between humans and land, is an individual and society as an inseparable unity (duality), that the fulfillment of one's needs for the land is placed within the framework of the needs of the whole community, so that the relationship is not merely individualistic, but rather collective while still providing place and respect for individual rights. Land management by the government, where the land registered in the territory of Indonesia will give a legal claim to the tutorial of the Republic of Indonesia (NKRI) in full. In addition, it is also to strengthen a harmonious national life by minimizing land dispute conflicts. This research is descriptive in nature, using a normative juridical approach. Data Analysis and Presentation, the data that has been obtained, both primary and secondary data, were analyzed using qualitative methods, namely by grouping data according to the aspects studied and conclusions that are relevant to the issues discussed. It is hoped that in the implementation of this gift, the related government will further improve services in terms of process and completion time. This is because there are many processes that must be passed in registering land. Where in the implementation of this transfer of land rights must go through several related agencies. It is hoped that the government will be more aggressive in providing awareness to the community by providing education on the legality of their lands and proof of their ownership so that there will be no future disputes. Providing knowledge to the wider community, especially the people of Padang City, of the completeness and correctness of their population data (such as the correctness of the data on their KTP), the completeness and correctness of their property data (one of which is their SPPT PBB).